Effects of Seasonal Variation on the Alkaloids of Different Ecotypes of Epichloë Endophyte-Festuca sinensis Associations - Lin, Weihu; Kuang, Yu; Wang, Jianjun; Duan, Dongdong; Xu, Wenbo; Tian, Pei; Nzabanita, Clement; Wang, Meining; Li, Miaomiao; Ma, Bihua (Frontiers in Microbiology, 2019)
The Epichloë endophyte–Festuca sinensis association produces alkaloids which can protect the host grass F. sinensis from biotic and abiotic stresses. Alkaloid concentrations depend on the genetic predisposition of grass and endophyte, and are affected by the environment. Endophyte infected six ecotypes F. sinensis cultivars were grown in experimental field and greenhouse for two year. Their above ground plant tissues were collected each season to test for peramine, lolitrem B and ergot concentrations. The results showed that seasonal changes affected the peramine, lolitrem B and ergot concentrations of Epichloë endophyte–F. sinensis associations; and these three different alkaloids responded differently to seasonal variation. The peramine concentration of six ecotypes F. sinensis decreased significantly (P < 0.05) from spring to autumn. The lolitrem B concentration of F. sinensis was higher in autumn than in other seasons. Five ecotypes (41, 57, 84, 99 and 141) of F. sinensis ergot concentrations peaked in the summer, and lowered in spring and autumn. In addition, the ecotype has insignificant effect (P > 0.05) on the peramine and lolitrem B concentrations of F. sinensis, but it has a significant impact (P < 0.05) on the ergot concentrations. We concluded that the seasonal variation and ecotypes can influence the alkaloids produced by the F. sinensis–endophyte associations, but the effects of seasonal conditions on the alkaloid concentrations are more pronounced than ecotypes.